Pengaruh Pemberian Silase Rumput Kume (Sorghum Plumosum Var. Timorense ) dan Alysicarpus Vaginalis dengan Imbangan yang Berbeda terhadap Pemanfaatan Energi pada Sapi Persilangan Ongole X Brahman - Lewerang, Agustinus Lewa; Jelantik, I Gusti N; Benu, Imanuel (Animal Agricultura, 2024)
The aim of this study was to determine the effect of giving silages of the mixture of different ratio of kume grass and Alysicarpus vaginalis on the intake of gross energy and digestibility of energy as well as metablisable energi in Ongole x Brahman cross cattle. This study used a Latin square design (RBSL) with 4 treatments and 4 periods as replications. The treatments used were: AV0: silage made of 100% kume grass, AV20: silage consisting of 80% + 20% kume grass Alysicarpus vaginalis, AV40: silage consisting of 60% + 40% kume grass Alisycarpus vaginalis, AV60: silage consisting of from kume grass 40% + 60% Alisycarpus vaginalis. The results of this study showed that feeding silage made of different ratio of kume grass silage and Alysicarpus vaginalis had significant effect (P<0.01) on energy intake, energy digestibility, and energy metabolism. The conclusion of this research is that feeding silage made of kume grass silage and Alysicarpus vaginalis in different ratio to cattle does not modify the energy utilization in Ongole.